Complete chloroplast genome sequence of Taxillus chinensis (Loranthaceae): a hemiparasitic shrub in South China - Liu, Bingbing (Mitochondrial DNA B Resour, 2019)
Taxillus chinensis (DC) Danser, which is a hemiparasitic shrub distributed in southern China and Southeast Asian countries, is wildly used in various traditional Chinese medicine prescriptions. In this study, the complete chloroplast genome of the T. chinensis was assembled from the whole genome Illumina sequencing data. The complete plastome is a typical quadripartite structure with a length of 121,305 bp, which contained two inverted repeats (IRs) of 22,460 bp separated by a large single-copy (LSC) and a small single copy (SSC) of 70,295 bp and 6090 bp, respectively. The plastome contains 106 genes, comprising 66 protein-coding genes, 28 tRNA genes, eight rRNA genes, and four processed pseudogenes. The overall GC content of the plastome is 37.4%, which is unevenly distributed across the whole chloroplast genome. The phylogenetic analysis shows that T. chinensis was closely related to the congeneric species T. sutchuenensis.